Out of the Lab and Into the World: Analyses of Social Roles and Gender in Profiles of Scientists in The New York Times and The Scientist - Benson-Greenwald, Tessa M.; Joshi, Mansi P.; Diekman, Amanda B. (Frontiers in Psychology, 2022)
Although representations of female scientists in the media have increased over time, stereotypical portrayals of science persist. In-depth, contemporary profiles of scientists’ roles have an opportunity to reflect or to challenge stereotypes of science and of gender. We employed content and linguistic analyses to examine whether publicly available profiles of scientists from New York Times and The Scientist Magazine support or challenge pervasive beliefs about science. Consistent with broader stereotypes of STEM fields, these portrayals focused more on agency than communality. However, profiles also challenged stereotypes through integrating communality, purpose, and growth. This analysis also found similar presence of communal and agentic constructs for both female and male scientists. The current findings highlight the importance of considering counterstereotypic representations of science in the media: Communicating messages to the public that challenge existing beliefs about the culture of science may be one path toward disrupting stereotypes that dissuade talented individuals from choosing science pathways.